Overcoming Project Delivery Delays in A Consulting Firm: A Knowledge Management Perspective - Claudia Ayu Putri (Institut Teknologi Sepuluh Nopember, 2020)
Based on Investment Coordinating Board (BKPM) press release, the investment realization in Indonesia for the period of 2015-2018 shows a positive trend. In addition, the issuance of Presidential Regulation No. 24 of 2018 related to Online Single Submission (OSS) which facilitates the issuance of licensing in Indonesia. This has a direct impact on the consulting firms, as the Foreign Investment Company (PT PMA) tends to transfer their internal activities to service provider companies to provide opportunities to fulfill their objectives to gain competitive advantage. Seeing this great potential, leads to growth in companies engaged in consulting. In Jakarta alone, there were at least 66 consulting firms which are working in similar field. During project completion, there are several obstacles causing delays in project delivery namely transfer of knowledge that was that was not carried out effectively due to changes in regulations. This research uses a qualitative method in the form of interviews processed through coding categorization, observation & archive at a consulting firm, BDO Indonesia. Furthermore, knowledge management systems, SECI and knowledge flow are presented. The result of this research shows the importance of knowledge management perspective to overcome the project delivery delays in the consulting firm.